ANALISIS ANALISIS WACANA KRITIS MODEL NORMAN FAIRCLOUGH PADA PEMBERITAAN CNN INDONESIA: “INDONESIA DAN BRASIL PERDALAMI KOLABORASI STRATEGIS SEKTOR ESDM" - Irlani Pratiwi; Tasya Meilani; Rizki Ahmad Hoerurido; Ahmad Fuadin (Jurnal Padamu Negeri, 2026)
This study aims to analyze news coverage concerning Indonesia and Brazil deepening strategic collaboration in the ESDM (Energy and Mineral Resources) sector as reported by CNN Indonesia. The study focuses on how language is used as a social practice in media discourse and on understanding the construction of reality built through such news discourse. This research employs a qualitative descriptive approach using Norman Fairclough's Critical Discourse Analysis (CDA) method. The research data consists of CNN Indonesia news texts analyzed through three dimensions: (1) text as a linguistic product, (2) discourse practice as the process of production-consumption of meaning, and (3) social practice as the broader ideological context. Based on the research findings, it can be concluded that the news not only forms a discourse that functions as an information conveyor but also serves as a mass media that reproduces the government's positive ideology. Through seemingly neutral representations, the media influences public perceptions of national progress, the transition to green energy, and global diplomacy between the two countries.